C–H Bond Formation with Boronic Acids and Derivatives by Transition-Metal-Free Conjugate Addition Reactions - Sánchez-Sancho, Francisco; Csákÿ, Aurelio G. (Synthesis, 2016)
Initially popularized by the Suzuki–Miyaura reaction, boronic acids, boronate esters, and trifluoroborates constitute nowadays essential reagents in C–C bond-forming processes. The classic transformations mediated by these reagents require the use of transition metals as catalysts. However, in recent times new reactions in which aryl, alkenyl, and alkynyl derivatives behave as nucleophiles in the absence of transition-metal catalysis have begun to emerge. The purpose of this review is to highlight the most relevant recent advances in C–C bond making reactions by conjugate addition of these types of boronic acids under transition-metal-free conditions.1 Introduction2 Nucleophilicity of Boronic Acid Derivatives3 Direct Conjugate Addition Reactions4 Activation with BF3, Cyanuric Fluoride, or TFAA5 Activation with BINOL Derivatives6 Activation with Tartaric Acid and Tartaric Acid Derivatives7 Conclusions
Keywords: boron; catalysis; conjugate addition; nucleophilic addition; transition-metal-free